Deranged liver function test after Covid 19 vaccination: a rare presentation with review of literature - Salma Salman; Khan, Tayyab; Iqbal, Sadia; Ahmed, Iftekhar; Tab-E-Rasool (Journal of the Pakistan Medical Association, 2023)
Word Health Organization declared Covid 19 infection as pandemic in 2020. Since then different countries had started working on vaccination. After multiple trials different vaccinations got approved. The first vaccine to be received in Pakistan was Sinopharm and was provided to nearly all health care professionals on priority basis. The safety profile of different vaccines were satisfactory and there were very few side effects reported till date. We are reporting the first case in Pakistan where a female health care professional developed vaccination induced deranged liver function test with delayed but complete recovery. Extensive workup was done to rule out all other differentials of deranged liver function test. Keyword: Vaccination, liver function test, Covid19.